Exploring the relationship between domain-specific self-efficacy and motivation among university students: a systematic review (2019–2024) - Lin, Luoting; Talib, Mansor Bin Abu (Frontiers in Psychology, 2025)
The interplay between domain-specific self-efficacy and motivation in higher education has garnered significant attention, particularly in the context of challenges such as the COVID-19 pandemic that have profoundly altered the educational landscape. This study provides a systematic review of the literature on the relationship between domain-specific self-efficacy and motivation among university students, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. From an initial pool of 5,890 articles sourced from the Education Resources Information Centre (ERIC), Scopus, and Web of Science (WoS) databases, 31 studies published between 2019 and 2024 were analyzed. Our findings underscore a predominantly positive correlation between domain-specific self-efficacy and motivation. Higher levels of self-efficacy are consistently linked to increased motivation, suggesting that enhancing self-efficacy could be a crucial strategy for boosting student motivation and, thus, academic success. Notably, many studies focus on Asian regions, highlighting both the universality and cultural specificity of these findings. However, the presence of an outlier study that found no significant relationship between self-efficacy and motivation indicates the complexity of these constructs and the potential impact of situational factors, warranting further investigation. Additionally, this review reveals a growing academic interest in self-efficacy and motivation, particularly within social sciences and education. This trend underscores the importance of a multidisciplinary approach to understanding the intricate dynamics between self-efficacy and motivation. The documented rise in research attention reflects a growing recognition of the critical role that self-efficacy and motivation play in student learning outcomes. In conclusion, this systematic review not only highlights the significant positive impact of domain-specific self-efficacy on student motivation but also calls for more nuanced studies. Future research should explore under-represented contexts and examine the broader implications of these findings across diverse educational and cultural settings.